THE IMPACT OF HOME LITERACY ENVIRONMENT ON THE THEME PREFERENCES IN THE NOVELS BY CHILD AUTHORS - Supri, Ida Zuraida; Ervina CM Simatupang; Hendar (English Review: Journal of English Education, 2025)
Children are naturally fond of stories that integrate meaning and humor yet engagingly deliver life principles and concepts. Stories provide not only entertainment but also a means of learning about various habits, cultures, and arrays of human experiences. In recent years, a remarkable shift has occurred in which children, previously passive consumers of stories, have become active contributors as child authors. In Bandung, the capital city of West Java capital city, a national publisher has emerged as a facilitator for child authors, allowing them to publish their creative works. This platform has published 536 novels written by young minds over the last two decades under the brand Kecil-Kecil Punya Karya (KKPK). This paper investigates the theme and genre preferred by child authors for their novels and to what extent immediate social factors influence their writing and topic preferences. This research may contribute valuable insights into the intersection of sociolinguistics, education, and societal influence by understanding the dynamics of child authorship. The results show that the themes preferred by the child authors are adventure and exploration, family and affection, friendship and mystery, and problem-solving. Immediate environment; family and school play a tremendous role in introducing, nurturing, and developing early literacy routines for child authors that lead to a positive productive literacy culture.